2017
DOI: 10.1177/1474515117692663
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing medical staff’s intentions to implement family-witnessed cardiopulmonary resuscitation: A cross-sectional, multihospital survey

Abstract: According to the findings of this study, it may be desirable for administrators to prioritize the implementation of the FWR policy in regional hospitals. We recommend affording the factors of positive attitudes and subjective norms high priority to improve the medical staff's behavioural intentions of FWR practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Another study, which reported that 48% of 124 ICU nurses with abundant CPR experience never advised families to be present during resuscitation and that 45% had only invited families 1–5 times, confirms that FPDR is primarily determined by healthcare providers (Powers & Candela, 2017). This is in line with the findings of a study with 1,122 healthcare providers in Taiwan, which reported that only 3.7% were supportive of the FPDR policy (Chen et al, 2017), and of a Brazilian study on inpatient ward nurses in a cardiology and pneumology department, which reported that 57.1% of the nurses mentioned that FPDR delayed the initiation of CPR and that 67.3% believed that it may have an adverse effect on CPR quality (Citolino Filho et al, 2015). However, these results differ from findings reported in the USA, where 67.8% of nurses (Helmer et al, 2000) and 77% of healthcare professionals (Lederman & Wacht, 2014) have allowed FPDR.…”
Section: Discussionsupporting
confidence: 91%
“…Another study, which reported that 48% of 124 ICU nurses with abundant CPR experience never advised families to be present during resuscitation and that 45% had only invited families 1–5 times, confirms that FPDR is primarily determined by healthcare providers (Powers & Candela, 2017). This is in line with the findings of a study with 1,122 healthcare providers in Taiwan, which reported that only 3.7% were supportive of the FPDR policy (Chen et al, 2017), and of a Brazilian study on inpatient ward nurses in a cardiology and pneumology department, which reported that 57.1% of the nurses mentioned that FPDR delayed the initiation of CPR and that 67.3% believed that it may have an adverse effect on CPR quality (Citolino Filho et al, 2015). However, these results differ from findings reported in the USA, where 67.8% of nurses (Helmer et al, 2000) and 77% of healthcare professionals (Lederman & Wacht, 2014) have allowed FPDR.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, EPBI is considered to be the intention of MHO staff to prepare so as to avoid losses from emergencies. As an essential theory to explain the general decision-making process of individual rational behavior, TPB is widely used in the field of behavioral science, and has been proved to have good explanatory and predictive power of human behavior, and can help researchers understand how people change their behavior patterns [11][12][13]. TPB holds that thoughtful and planned behavior comes from behavior intention, which depends on people's attitude towards behavior, subjective norms, and perceived behavioral control [14].…”
Section: Introductionmentioning
confidence: 99%
“…49,50 Chen et al recommended the implementation of family-witnessed CPR policies in Taiwanese regional hospitals, demonstrating that family-witnessed CPR is gaining attention in Asian countries. 51 From a patient perspective, a qualitative study highlighted that successfully resuscitated patients were supportive of having their family members witnessing their CPR in terms of the emotional support and the advocacy of the family. 52 A recent cross-sectional study confirmed these results.…”
Section: Discussionmentioning
confidence: 99%